Genetic Variations of Circulating Adiponectin Levels Modulate Changes in Appetite in Response to Weight-Loss Diets - W. Ma; Huang, T.; Heianza, Y.; T. Wang; Sun, D.; Tong, J.; Williamson, D. A.; Bray, G. A.; Sacks, F. M.; Qi, L. (J Clin Endocrinol MetabJ Clin Endocrinol MetabJ Clin Endocrinol Metab, 2017)
Context: Adiponectin plays key roles in regulating appetite and food intake. Objective: To investigate interactions between the genetic risk score (GRS) for adiponectin levels and weight-loss diets varying in macronutrient intake on long-term changes in appetite and adiponectin levels. Design, Setting, and Participants: A GRS was calculated based on 5 adiponectin-associated variants in 692 overweight adults from the 2-year Preventing Overweight Using Novel Dietary Strategies trial. Main Outcome Measures: Repeated measurements of plasma adiponectin levels and appetite-related traits, including cravings, fullness, prospective consumption, and hunger. Results: Dietary fat showed nominally significant interactions with the adiponectin GRS on changes in appetite score and prospective consumption from baseline to 6 months (P for interaction = 0.014 and 0.017, respectively) after adjusting for age, sex, ethnicity, baseline body mass index, and baseline respective outcome values. The GRS for lower adiponectin levels was associated with a greater decrease in appetite (P < 0.001) and prospective consumption (P = 0.008) among participants consuming a high-fat diet, whereas no significant associations were observed in the low-fat group. Additionally, a significant interaction was observed between the GRS and dietary fat on 6-month changes in adiponectin levels (P for interaction = 0.021). The lower GRS was associated with a greater increase in adiponectin in the low-fat group (P = 0.02), but it was not associated with adiponectin changes in the high-fat group (P = 0.31). Conclusions: Our findings suggest that individuals with varying genetic architecture of circulating adiponectin may respond divergently in appetite and adiponectin levels to weight-loss diets varying in fat intake.
Keywords: *Diet, Reducing; Adiponectin/*blood/*genetics; Adult; Appetite/drug effects/*physiology; Biomarkers/analysis; Early Medical Intervention; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Overweight/blood/*drug therapy/genetics; Polymorphism, Single Nucleotide/*genetics; Prognosis; Weight Loss/*drug effects/genetics